Influence of tool steel alloying elements Mo and Ni on the formation of the interaction layer between tool steels and molten aluminium alloys - Vončina, Maja; Balaško, Tilen; Medved , Jožef; Nagode, Aleš (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
The dissolution of tool steels in molten aluminium alloys is affected by the presence of alloying elements in both the molten aluminium and the tool steel. The present work was carried out to predict the effect of tool steel alloying elements, mostly Ni and Mo, on the interaction layer formed between tool steel and molten aluminium alloy. The interaction layer between the investigated tool steels Dievar or RavnexHD and Al99.9 and Al99.7 aluminium alloy consists of an intermetallic and a composite layer. The interaction layer between the investigated tool steels and the AlSi12 aluminium alloy consists of three different interaction layers. The better solubility resistance in various molten aluminium alloys shows hot-work tool steel RavnexHD. The main alloying element in the tool steels investigated, that influence on the dissolution of tools teel in molten aluminium is Ni, which is present in higher amounts in RavnexHD. Ni incorporate in the matrix, inhibits the diffusion of iron and aluminium through the matrix. Mo in Dievar tool steel forms carbides, allowing easier diffusion of these elements through the Fe-matrix.